Pyroglutamyl peptidase type I from Trypanosoma brucei: A new virulence factor from African trypanosomes that de-blocks regulatory peptides in the plasma of infected hosts - Morty, R.E.; Bulau, P.; Pelle, Roger; Wilki, S.; Abe, K. (Portland Press Ltd., 2006)
Peptidases of parasitic protozoans are emerging as novel virulence factors and therapeutic targets in parasitic infections. A trypanosome-derived aminopeptidase that exclusively hydrolysed substrates with Glp (pyroglutamic acid) in P1 was purified 9248-fold from the plasma of rats infected with Trypanosoma brucei brucei. The enzyme responsible was cloned from a T. brucei brucei genomic DNA library and identified as type IPGP (pyroglutamyl peptidase), belonging to the C15 family of cysteine peptidases. We showed that PGP is expressed in all life cycle stages of T. brucei brucei and is expressed in four other blood-stream-form African trypanosomes. Trypanosome PGP was optimally active and stable at bloodstream pH, and was insensitive to host plasma cysteine peptidase inhibitors. Native purified and recombinant hyper-expressed trypanosome PGP removed the N-terminal Glp blocking groups from TRH (thyrotrophin-releasing hormone) and GnRH (gonadotropin-releasing hormone) with a kcat/Km value of 0.5 and 0.1 s-1 · µM-1 respectively. The half-life of TRH and GnRH was dramatically reduced in the plasma of trypanosome-infected rats, both in vitro and in vivo. Employing an activity-neutralizing anti-trypanosome PGP antibody, and pyroglutamyl diazomethyl ketone, a specific inhibitor of type I PGP, we demonstrated that trypanosome PGP is entirely responsible for the reduced plasma half-life of TRH, and partially responsible for the reduced plasma half-life of GnRH in a rodent model of African trypanosomiasis. The abnormal degradation of TRH and GnRH, and perhaps other neuropeptides N-terminally blocked with a pyroglutamyl moiety, by trypanosome PGP, may contribute to some of the endocrine lesions observed in African trypanosomiasis.